Sources for the Study of Food Prices in the Spanish Municipal Archives at the Modern Age: The Legal Books of the Faithful Executors of Toledo - García Ruipérez, Mariano (Cuadernos de Historia Moderna, 2017)
The study of food prices in Modern Spain is based on documents preserved in the municipal archives. It was carried out with the help of the books of agreements and the procurement records for the basic supplies. Few town halls, perhaps only Madrid and Toledo, have preserved record books in which is reflected the activity of the faithful executors. They were in charge of setting the price of the goods that came to the market, controlling their quality or inspecting their weights and measurements. These books registered the reports and penalties that incurred the offenders. Furthermore they contained the biddings adopted every day, along with the customs tariff. They constitute a source of exceptional and undeveloped documentary that can be used in projects of economic history, social history, internal trade, eating habits, evolution of prices, agrarian crises, etc.